Noncanonical role for the host Vps4 AAA+ ATPase ESCRT protein in the formation of Tomato bushy stunt virus replicase. - Daniel Barajas; Isabel Fernández de Castro Martín; Judit Pogany; Cristina Risco; Peter D Nagy (PLoS Pathogens)
Assembling of the membrane-bound viral replicase complexes (VRCs) consisting of viral- and host-encoded proteins is a key step during the replication of positive-stranded RNA viruses in the infected cells. Previous genome-wide screens with Tomato bushy stunt tombusvirus (TBSV) in a yeast model host have revealed the involvement of eleven cellular ESCRT (endosomal sorting complexes required for transport) proteins in viral replication. The ESCRT proteins are involved in endosomal sorting of cellular membrane proteins by forming multiprotein complexes, deforming membranes away from the cytosol and, ultimately, pinching off vesicles into the lumen of the endosomes. In this paper, we show an unexpected key role for the conserved Vps4p AAA+ ATPase, whose canonical function is to disassemble the ESCRT complexes and recycle them from the membranes back to the cytosol. We find that the tombusvirus p33 replication protein interacts with Vps4p and three ESCRT-III proteins. Interestingly, Vps4p is recruited to become a permanent component of the VRCs as shown by co-purification assays and immuno-EM. Vps4p is co-localized with the viral dsRNA and contacts the viral (+)RNA in the intracellular membrane. Deletion of Vps4p in yeast leads to the formation of crescent-like membrane structures instead of the characteristic spherule and vesicle-like structures. The in vitro assembled tombusvirus replicase based on cell-free extracts (CFE) from vps4Δ yeast is highly nuclease sensitive, in contrast with the nuclease insensitive replicase in wt CFE. These data suggest that the role of Vps4p and the ESCRT machinery is to aid building the membrane-bound VRCs, which become nuclease-insensitive to avoid the recognition by the host antiviral surveillance system and the destruction of the viral RNA. Other (+)RNA viruses of plants and animals might also subvert Vps4p and the ESCRT machinery for formation of VRCs, which require membrane deformation and spherule formation.